Distribution of Arsenic Resistance Genes in Prokaryotes - Ben Fekih, Ibtissem; Zhang, Chengkang; Li, Yuan Ping; Zhao, Yi; Alwathnani, Hend A.; Saquib, Quaiser; Rensing, Christopher; Cervantes, Carlos (Frontiers in Microbiology, 2018)
Arsenic is a metalloid that occurs naturally in aquatic and terrestrial environments. The high toxicity of arsenic derivatives converts this element in a serious problem of public health worldwide. There is a global arsenic geocycle in which microbes play a relevant role. Ancient exposure to arsenic derivatives, both inorganic and organic, has represented a selective pressure for microbes to evolve or acquire diverse arsenic resistance genetic systems. In addition, arsenic compounds appear to have been used as a toxin in chemical warfare for a long time selecting for an extended range of arsenic resistance determinants. Arsenic resistance strategies rely mainly on membrane transport pathways that extrude the toxic compounds from the cell cytoplasm. The ars operons, first discovered in bacterial R-factors almost 50 years ago, are the most common microbial arsenic resistance systems. Numerous ars operons, with a variety of genes and different combinations of them, populate the prokaryotic genomes, including their accessory plasmids, transposons, and genomic islands. Besides these canonical, widespread ars gene clusters, which confer resistance to the inorganic forms of arsenic, additional genes have been discovered recently, which broadens the spectrum of arsenic tolerance by detoxifying organic arsenic derivatives often used as toxins. This review summarizes the presence, distribution, organization, and redundance of arsenic resistance genes in prokaryotes.